2020
DOI: 10.1016/j.ajog.2020.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean radical hysterectomy for cervical cancer in the United States: a national study of surgical outcomes

Abstract: Cesarean radical hysterectomy (cesarean-RH) is performed at the time of cesarean delivery for pregnant women with early-stage cervical cancer. 1 Cesarean-RH is a rare procedure and has been understudied; population statistics are lacking in the literature. This study examined the characteristics and perioperative outcomes of women with cervical cancer who underwent cesarean-RH. STUDY DESIGN: This is a population-based retrospective study that queried the Healthcare Cost and Utilization Project's National Inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
7
1
Order By: Relevance
“…Six women who had a CS combined with a radical hysterectomy had statistically significantly higher estimated blood loss compared to eight women who had a postpartum radical hysterectomy (2033 vs 425 mL; P = 0.0064), although there was no difference in blood transfusions or surgical complications. On the contrary, a recently published populationbased study by Matsuo et al found an increase in total perioperative morbidity in 257 patients with a combined procedure compared to 15,420 patients who underwent an open radical hysterectomy [7]. The increased total perioperative morbidity for the combined group in this study was mainly caused by an increase in perioperative blood loss with an incidence of 27.1% vs 13.8% in the control group.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Six women who had a CS combined with a radical hysterectomy had statistically significantly higher estimated blood loss compared to eight women who had a postpartum radical hysterectomy (2033 vs 425 mL; P = 0.0064), although there was no difference in blood transfusions or surgical complications. On the contrary, a recently published populationbased study by Matsuo et al found an increase in total perioperative morbidity in 257 patients with a combined procedure compared to 15,420 patients who underwent an open radical hysterectomy [7]. The increased total perioperative morbidity for the combined group in this study was mainly caused by an increase in perioperative blood loss with an incidence of 27.1% vs 13.8% in the control group.…”
Section: Discussioncontrasting
confidence: 80%
“…Comparing morbidity in one surgical group versus another demands matching for variables impacting on morbidity, such as radicality of the procedure, tumour size and stage of disease. Unfortunately, this was not done in both previous mentioned studies [7,16].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the procedure is associated with a higher rate of blood loss, intra-operative hemorrhage, and blood transfusions [ 38 ]. Despite this finding, the rate of other operative and post-operative complications appears to be comparable to that of a non-pregnant radical hysterectomy or with the fetus in situ [ 39 ], as does the surgical mortality rate [ 40 ]. In our experience, 11 of 13 patients (84.6%) performed CRH.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates section and grouping as well as measured outcomes were consistent with our prior studies [28][29][30], and a complete list of the ICD-9 codes was described previously [28][29][30]. Data variables abstracted from the NIS program included: patient demographics, hospital characteristics, gynecologic disease type, surgical procedure type, and perioperative outcomes.…”
Section: Clinical Datamentioning
confidence: 99%